Territoires de libération : perspectives féministes musulmanes - Benhadjoudja, Leïla (Tumultes, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discipline; discours dominant; fem3400; féminisme islamique; féminisme musulman; histoire et politique; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques

De la recherche sur les féminismes musulmans : enjeux de racisation et de positionnement - Benhadjoudja, Leila (Le sujet du féminisme est-il blanc? : femmes racisées et recherche féministe, 2015)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; cours; fem3400; féminisme islamique; intersectionnalité; premier cycle; privilèges; périodes historiques; québec; racisme; régions géographiques; systèmes d'oppressions

Chroniques d'une musulmane indignée - Ibnouzahir, Asmaa (Fides, 2015)
En plus d'un récit autobiographique racontant les défis qu'elle a relevés en tant que jeune immigrante musulmane d'origine marocaine arrivée au Québec en 1994, Asmaa Ibnouzahir présente également une analyse éclairante sur des questions qui reviennent souvent dans nos médias au sujet de l'islam, des femmes et de la société: les musulmans «modérés», les crimes «d'honneur», le foulard, le féminisme islamique et bien d'autres. Islamiste pour certains et hérétique pour d'autres, Asmaa Ibnouzahir partage avec nous son parcours personnel et militant qui a fait d'elle la citoyenne québécoise musulmane, féministe et indignée qu'elle est aujourd'hui. Engagée dans les débats sociopolitiques qui ont traversé le Québec au cours de la dernière décennie, sur la religion, l'immigration et les valeurs québécoises, Asmaa Ibnouzahir livre un témoignage essentiel qui donne un accès sans précédent aux coulisses de ces débats. Depuis une dizaine d'années, Asmaa Ibnouzahir est engagée dans la réflexion et les débats sociaux autour des droits de la personne, notamment sur les questions touchant autant à l'immigration et à la religion dans la sphère publique qu'au statut des femmes dans l'Islam. Elle a également voyagé et travaillé dans plus d'une quinzaine de pays en tant que spécialiste de la nutrition d'urgence humanitaire. -- [Renaud-Bray].
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; amériques; approches et analyses; canada; com5170; corps; cours; discipline; droits des femmes*; droits des personnes; féminisme islamique; immigration; maroc; point de vue situé; premier cycle; périodes historiques; québec; religion; régions géographiques; science politique; science politique et droit; thématiques

"Deveiling" Body Stories: Muslim Girls Negotiate Visual, Spatial, and Ethical "Hijabs" - Hamzeh, Manal (Race, Ethnicity and Education, 2011)
This article describes a collaborative research project that took place in two south‐western US border towns and sought to understand how four muslim Footnote 1 girls (age 14–17) expressed and negotiated their bodily learning experiences. Drawing on both the work of arab–muslim critical feminist Fatima Mernissi who utilized classical Islamic tools of research and my positionalities as arabyyah‐muslimah, I used insider’s methods to discuss how three hijabs (veils) – the visual, spatial, and ethical – acted as a central genderizing discourse that challenged the girls’ learning opportunities. This article shows how the girls’ parents enforced these three hijabs; how the girls questioned and deveiled the hijabs in their dress, mobility in public places, and physical behavior around boys. This inquiry is a call for critical feminist researchers and educators to recognize how these three hijabs form a key genderizing discourse in the lives of muslim girls. It also presents the importance of: (1) working with muslim girls as agents in their own lives; (2) critical engagement with difference between researchers/educators and muslim communities; and (3) practicing a critically reflexive pedagogy of deveiling.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; corps; cours; discipline; féminisme islamique; point de vue situé; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; thématiques; états-unis; états-unis (sud)

Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis

Unveiled Sentiments: Gendered Islamophobia and Experiences of Veiling among Muslim Girls in a Canadian Islamic School - Zine, Jasmin (Equity & Excellence in Education, 2006)
The practice of veiling has made Muslim women subject to dual oppressions--racism and Islamophobia--in society at large and patriarchal oppression and sexism from within their communities. Based on a narrative analysis of the politics of veiling in schools and society, the voices of young Muslim women attending a Canadian Islamic school speak to the contested notion of gender identity in Islam. The narratives situate their various articulations of Islamic womanhood in ways that both affirm and challenge traditional religious notions. At the same time they also are subject to Orientalist representations of veiled and burqa clad women that represent them as oppressed and backward. Focusing on ethnographic accounts of veiling among Muslims girls who attended a gender-segregated Islamic high school in Toronto, this discussion allows a deeper understanding of how gendered religious identities are constructed in the schooling experiences of these Muslim youth. (Contains 11 notes.)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; corps; cours; discipline; féminisme islamique; intersectionnalité; islamophobie; ontario; patriarcat; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; toronto; voiles islamiques